2019
DOI: 10.1371/journal.pone.0211955
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring quality of obstetric care from hospital discharge databases: A Delphi survey to propose a new set of indicators based on maternal health outcomes

Abstract: Objectives Most indicators proposed for assessing quality of care in obstetrics are process indicators and do not directly measure health effects, and cannot always be identified from routinely available databases. Our objective was to propose a set of indicators to assess the quality of hospital obstetric care from maternal morbidity outcomes identifiable in permanent hospital discharge databases. Methods Various maternal morbidity outcomes potentially reflecting quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…It is known that maternal mortality is underreported, that definitions differ across countries, and that in some countries, separate registers exist to record maternal mortality and many national registers do not register maternal mortality until 42 days [21,22]. Previous studies recommended that increased attention should be paid to registering maternal morbidity more accurately [23,24]. In addition, low incidences of Apgar score < 7 in Malta and Chile and PPH in Malta may be a result of underreporting [25,26].…”
Section: Plos Medicinementioning
confidence: 99%
“…It is known that maternal mortality is underreported, that definitions differ across countries, and that in some countries, separate registers exist to record maternal mortality and many national registers do not register maternal mortality until 42 days [21,22]. Previous studies recommended that increased attention should be paid to registering maternal morbidity more accurately [23,24]. In addition, low incidences of Apgar score < 7 in Malta and Chile and PPH in Malta may be a result of underreporting [25,26].…”
Section: Plos Medicinementioning
confidence: 99%
“…There is no global consensus on which maternal and perinatal indicators should be chosen to represent quality and outcomes of maternity care [16], these indicators were chosen to reflect and correspond with a number of reviews on the topic [16][17][18], as well as to fit data that is routinely recorded and available at Mpilo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with respect to the quality of care, we found that the HCAHPS measures either fell out of our model or if included, did not explain a statistically significant proportion of the SNH/non‐SNH disparity in postpartum readmissions. More proximal measures of obstetric care quality are needed 38–40 …”
Section: Discussionmentioning
confidence: 99%